Myoxinol (Hydrolyzed Hibiscus esculentus Extract) in the Cure of Chronic Anal Fissure: Early Clinical and Functional Outcomes - Adolfo Renzi; Antonio Brillantino; Giandomenico Di Sarno; Francesco D’Aniello; Stefania Ziccardi; Fiorella Paladino; Francesca Iacobellis (Gastroenterology Research and Practice)
Objective. This study was designed to evaluate the early results of the topical application of Hydrolyzed Hibiscus esculentus Extract 3% ointment (Myoxinol 3%), a novel local product with Botox-like activity, in the conservative treatment of chronic anal fissure (CAF). Methods. Among all patients with CAF observed during the study period, 31 subjects met the inclusion criteria and underwent medical therapy with Myoxinol 3% ointment every 12 hours for 6 weeks. Two patients were lost to follow-up. Clinical and manometric follow-up was carried out eight weeks after treatment. Results. At follow-up the success rate was 72.4% (21/29); median VAS score and mean anal resting pressure were significantly lower if compared with respective baseline data. The only one adverse effect of the topical application of Myoxinol 3% ointment was perianal itch, which was reported by 3,4% (1/29) of the patients available for the analysis. However, in this case this symptom did not cause interruption of the treatment. Conclusions. The topical application of Myoxinol 3% ointment in the cure of CAF shows encouraging early results. Further researches with a larger series and a longer follow-up are needed to confirm these data.